Pengendalian Penyakit Edwardsiellosis Menggunakan Vaksin Alami pada Budidaya Ikan Patin (Pangasius pangasius) - Ingka Selviana; Imam Majid; Krisna Al-Rasyidin; Muhammad Madhat Husayn; Reyfaldo Tyo Wijaya; Madyasta Anggana Rarassari (Seminar Nasional Lahan Suboptimal, 2021)
Selviana I, Majid I, Al-Rasyidin K, Husayn MM, Wijaya RT, Rarassari MA. 2021. Edwardsiellosis disease control using natural vaccines in catfish (Pangasius pangasius) cultivation. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 697-704.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Catfish (Pangasius pangasius) is the leading freshwater consumption fish that is widely cultivated. Various efforts have been made to increase catfish production, one of which is the intensification of cultivation. However, catfish are very susceptible to Edwardsielliosis disease caused by the bacterium Edwarsiella tarda, so that it can cause death to fish. E. tarda infection can cause high enough mortality, causing a decrease in productivity in catfish and can cause losses for fish farmers. This study aims to identify edwarsiellosis disease with natural vaccines in catfish (P. pangasius) aquaculture. So the result of this study to treat edwardsiellosis is the administration of natural vaccines, although it is not as effective as treating extracellular with various methods that have been used to develop effective vaccines against edwardsiellosis. Microbiological testing was carried out on samples of kidney, liver, and brain organs taken at random from catfish infected with the bacterium Edwardiella tarda. So there is a need for natural vaccines, because vaccines have gradually become the main product in disease prevention in catfish (P. pangasius) aquaculture. So it can be concluded that catfish (P. pangasius) infected with edwardsiellosis disease can be treated using natural vaccines in catfish culture so that farmers do not experience losses and become an inhibiting factor for the success of catfish cultivation. It is hoped that the community or catfish cultivators can pay attention and carry out good and clean cultivation so that the fish that are cultivated do not become infected with edwardsiellosis disease.